In vivo targeting of protein antigens to dendritic cells using anti‐DEC‐205 single chain antibody improves HIV Gag specific CD4+ T cell responses protecting from airway challenge with recombinant vaccinia‐gag virus. Issue 2 (13th March 2017) - Ngu, Loveline N.; Nji, Nadesh N.; Ambada, Georgia E.; Sagnia, Bertrand; Sake, Carol Ngane; Tchadji, Jules Colinc; Njambe Priso, Ghislain Donald; Lissom, Abel; Tchouangueu, Thibau Flaurant; Manga Tebit, Denis; Waffo, Alain Bopda; Park, Chae Gyu; et al.
Abstract: Introduction: Targeting antigens to dendritic cells (DCs) in vivo via a DC‐restricted endocytic receptor, DEC205, has been validated to enhance immunity in several vaccine platforms. Particularly atttractive is selected delivery of proteins to DCs in vivo because it enables proteins to be more immunogenic and provides a cheaper and effective way for repeated immunizations. Methods: In this study, we tested the efficacy of a single chain antibody to DEC205 (scDEC) to deliver protein antigens selectively to DCs in vivo and to induce protective immunity. Results: In comparison to soluble Ovalbumin (OVA) antigen, when recombinant scDEC:OVA protein was injected subcutaneously (s.c.) into mice, the OVA protein was selectively presented by DCs to both TCR transgenic CD8 + and CD4 + T cells approximately 500 and 100 times more efficient than soluble OVA, respectively, and could persist for seven days following s.c. injection of the scDEC205:OVA. Similarly selective targeting of HIV Gag P24 to DCs in vivo using scDEC‐Gag protein plus polyICLC vaccine resulted in strong, long lasting, polyfuntional CD4 + T cells in mice which were protective against airway challenge by a recombinant vaccinia‐gag virus. Conclusion: Thus targeting protein antigens to DCs using scDEC can be used either alone or in combination with other strategies for effective immunization. Abstract : Targeting protein antigen in situ to dendritic cells using single chain antibody to DEC205 enhanced antigen uptake and presentation. combining such targeting with a TLR3 ligand polyICLC enables the induction of protective CD4 + T cells in murine airway.